A density functional study on the reactivity enhancement induced by gold in IrAu nanoalloys - Cappellari, Paula Sofía (2018)
IrAu nanoalloys have been proven to have remarkable reactivity for several reactions. In this work, mixed IrAu nanoalloys of 8, 27, 48 and 64 total atoms were studied in different atomic compositions (IrmAun) using Density Functional Theory (DFT). A notable segregation tendency is observed, where Ir atoms are located in the inner part and Au atoms in the outermost region of the nanostructure. We found that IrAu nanoalloys present a distinctive synergistic effect with respect to reactivity. In addition, the projected density of electronic states (PDOS) energies were analyzed by examining the d-band shift to estimate the reactivity of various IrAu nanoalloys. Furthermore, the adsorption energies for the CO molecule in the domains of the Ir-Au interface were evaluated. In this sense, the addition of Au atoms to Ir clusters increases the reactivity of Ir by generating unoccupied orbitals near the Fermi level as indicated by the PDOS study.